2009
DOI: 10.1002/anie.200806058
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Carbon Dioxide into Methanol with Silanes over N‐Heterocyclic Carbene Catalysts

Abstract: Activate and reduce: Carbon dioxide was reduced with silane using a stable N-heterocyclic carbene organocatalyst to provide methanol under very mild conditions. Dry air can serve as the feedstock, and the organocatalyst is much more efficient than transition-metal catalysts for this reaction. This approach offers a very promising protocol for chemical CO(2) activation and fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
330
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(344 citation statements)
references
References 41 publications
9
330
0
5
Order By: Relevance
“…The last 2-3 years have seen a rapid increase in the number of publications, with many proposed new routes for activating CO 2 using homogeneous catalysts [49], for example -hydrosilanes used to convert CO 2 into methane or methanol using zirconium phenoxide borane complexes or N-heterocyclic carbenes as catalysts [50,51]; -borane reduction of CO 2 to form boryl formats using nickel diphosphine complexes as catalysts [52]; [53,54]; -non-metal-mediated homogeneous hydrogenation of CO 2 to CH 3 OH [55]; and -indirect conversion of CO 2 to methanol based on the use of Ru pincer complexes as catalysts for the hydrogenation of carbonates, carbamates and formats [56].…”
Section: (D) New Routes For Co 2 Utilizationmentioning
confidence: 99%
“…The last 2-3 years have seen a rapid increase in the number of publications, with many proposed new routes for activating CO 2 using homogeneous catalysts [49], for example -hydrosilanes used to convert CO 2 into methane or methanol using zirconium phenoxide borane complexes or N-heterocyclic carbenes as catalysts [50,51]; -borane reduction of CO 2 to form boryl formats using nickel diphosphine complexes as catalysts [52]; [53,54]; -non-metal-mediated homogeneous hydrogenation of CO 2 to CH 3 OH [55]; and -indirect conversion of CO 2 to methanol based on the use of Ru pincer complexes as catalysts for the hydrogenation of carbonates, carbamates and formats [56].…”
Section: (D) New Routes For Co 2 Utilizationmentioning
confidence: 99%
“…However, the possibility of catalytically generating hydrides and drive the reduction all the way to methoxides engenders a resurgence of interest for these concepts as they could potentially be extrapolated to CO2 hydrogenation strategies. The first example of metal-free catalytic reduction of carbon dioxide was reported by Ying and coworkers in 2009 when they demonstrated that N-heterocyclic carbenes can catalyze the hydrosilylation of CO2 to methoxysilanes [52]. While the mechanism is debated [53][54], recently published computations suggest that the NHC-CO2 adduct serves as a Lewis base in order to activate silanes by hyper-coordination, thus favoring hydride transfer [55].…”
Section: Rationalizing the Catalytic Activity Of Ambiphilic Moleculesmentioning
confidence: 99%
“…Recently, the pace with which organocatalytic procedures are being utilized in organic preparations that involve CO 2 as a key reagent is unquestionably increasing. There are a number of structurally different organocatalyst systems that are considered as catalytic mediator including those based on ionic liquids (ILs), [33][34][35] N-heterocyclic carbenes (NHCs), 36 phenolic compounds 37 and sophisticated azaphosphatranes. 38 This is a true testimony of the increasing prominence of organocatalysis in the area of CO 2 fixation to create value-added organic matter from a waste material.…”
Section: Introductionmentioning
confidence: 99%